Pembacaan Dangding Haji Hasan Mustapa terhadap Sastra Sufistik Sunda di Era Budaya Popular - Jajang A. Rohmana (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2013)
Dangding as a literary work is only meaningful when chanted. When one just reads in his/her mind silently, dangding becomes dry and lacks of meaning. This paper discusses the position of Mustapa?s dangding in literary context and their relevance to contemporary Sundanese discourse. The main focus of this study is the character of his mystical verses, structural aspects of dangding as a Sufism vessel, and to examine any discrepancy of meaning in reading process on his dangding for Sundanese literary today. Cultural studies approach is used to analyze the meaningfulness of his works in the current widespread popular cultural challenges. The study finds that with the decline of dangding tradition, Mustapa?s works receive a great deal of challenges seen from the development of modern literary: the influence of Indonesian literature (short stories, novels, etc.) to the Sundanese literary; dangding becomes marginalized along with the loss of many cultural institutions where it is appreciated; and the problem of meaning discrepancies on reading it in popular culture, which is dominated by massively printed works that lost the meaning behind words and melody. It is difficult for it to compete in popular cultural hegemony that relies on uniformity, profit-oriented and passive consumer.